On Approximating the Toader Mean by Other Bivariate Means - Jun-Li Wang; Wei-Mao Qian; Zai-Yin He; Yu-Ming Chu (Journal of Function Spaces)
In the article, we provide several sharp bounds for the Toader mean by use of certain combinations of the arithmetic, quadratic, contraharmonic, and Gaussian arithmetic-geometric means.